2018
DOI: 10.1111/jwas.12521
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phosphorus Requirement of Fingerling Indian Major Carp, Labeo rohita (Hamilton)

Abstract: Dietary phosphorus requirement of fingerling Labeo rohita (6.1 ± 0.13 cm; 1.88 ± 0.05 g) was quantified by feeding seven isonitrogenous (350 g/kg crude protein) and isocaloric (16.72 kJ/g gross energy) purified diets with different levels of phosphorus as 3.5 (basal diet), 4.6, 5.7, 6.5, 7.8, 8.9, and 10.1 g/kg. Triplicate groups of fish were fed at 0800, 1200, and 1600 h to apparent satiation for 8 wk. Live weight gain (LWG; 494.68%), specific growth rate (3.18%/d), feed conversion ratio (1.54), feed efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
4
13
0
Order By: Relevance
“…Similar results have also been reported in white shrimp (Pan et al, 2005) and Chinese mitten crab ( Eriocheir sinensis ) (Chen et al, 2014; Lei et al, 2020). Dietary P deficiency may depress the β‐oxidation of fatty acids which was associated with the amount of ATP (Musharraf & Khan, 2018). Some studies on fish and crustaceans suggested that the mRNA expressions of lipid metabolism enzymes were affected by dietary P levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have also been reported in white shrimp (Pan et al, 2005) and Chinese mitten crab ( Eriocheir sinensis ) (Chen et al, 2014; Lei et al, 2020). Dietary P deficiency may depress the β‐oxidation of fatty acids which was associated with the amount of ATP (Musharraf & Khan, 2018). Some studies on fish and crustaceans suggested that the mRNA expressions of lipid metabolism enzymes were affected by dietary P levels.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus (P), a required nutrient in fish diet, is a limit factor that causes the deterioration of aquatic environment due to the P discharging from the feed and faeces because of the excessive P supplementation in fish diet (Hua & Bureau, ; Sugiura, Dong, & Hardy, ), whereas P is an essential nutrient required for growth, skeletal mineralization, reproduction and energy metabolism in fish, and is critical to be added into fish diets because fish have the low availability of P in both freshwater and seawater (Lall, ; NRC, ; Roy & Lall, ; Sugiura, Hardy, & Roberts, ). Therefore, to minimize eutrophication of waterbody, aquafeeds should meet the P requirement of fish and avoid excess P contents in the diet at the meantime (Jokinen, Vielma, Aaltonen, & Koskela, ; Musharraf & Khan, ). The studies about P requirement and utilization have been largely reported in many fish species, such as large yellow croaker ( Pseudosciaena crocea R. ) (Mai et al, ), rainbow trout ( Oncorhynchus mykiss ) (Fontagné et al, ; Lellis, Barrows, & Hardy, ), juvenile black seabream ( Sparus macrocephalus ) (Shao et al, ), Africa catfish ( Heterobranchus bidorsalis ) (Nwanna, Adebayo, & Omitoyin, ), stinging catfish ( Heteropneustes fossilis ) (Zafar & Khan, ) and gibel carp ( Carassius auratus gibelio ) (Xie et al, , ), which, however, have rarely been studied in sturgeon.…”
Section: Introductionmentioning
confidence: 99%
“…When phosphorus levels in the ration are excessive, the efficiency of its use decreases considerably, increasing its excretion into the environment and contributing to the eutrophication of the aquatic environment. Because of this, it is necessary to adjust the dietary concentration of the element to strictly meet, but not exceed, nutritional requirements (FURUYA et al, 2010;TANG et al, 2012;MUSHARRAF;KHAN, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in weight gain was observed until the estimated digestible phosphorus level reached 0.64%, associated with consumption of similar feed and a linear increase in phosphorus consumption, implying an improvement of feed:gain ratio. This indicates that increased phosphorus in the diet promoted an improvement in the use of nutrients, especially for protein deposition, as lean tissue deposition (protein) is more energy efficient than fat deposition because protein incorporates more water in its composition (NOBLET et al, 2001;BOMFIM et al, 2010;SOUSA et al, 2018;MUSHARRAF;KHAN, 2019), thus minimizing the excretion of nitrogenous residues to the environment (BOMFIM 2013).…”
mentioning
confidence: 99%